Sharia Peer-to-Peer Lending Financing : A Funding Alternative for MSMEs in Indonesia - Desky, Harjoni; Savitri, Asmah (Al-Hiwalah: Journal of Sharia Economic Law, 2024)
Sharia-based Peer-to-Peer (P2P) lending has become one of the funding alternatives for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia that have limited access to capital from conventional banks. By using Sharia principles, this P2P lending aims to provide funding services that follow Islamic values and are open to MSME players. Research objectives: This study aims to analyze the role, effectiveness, and challenges of Islamic P2P lending financing in supporting the development of MSMEs in Indonesia and assess its compliance with Islamic economic principles. Research method: This research uses a qualitative approach with a literature study method and in-depth interviews with several MSME players and Islamic P2P lending service providers. Secondary data were obtained from reports and publications of the Islamic fintech industry, while primary data were collected through interviews that were thematically analyzed. Research results: The results show that Islamic P2P lending financing can provide significant alternative funding for MSMEs in Indonesia, especially in terms of accessibility and flexibility. However, there are challenges related to regulation and public education on Islamic financing. The Sharia-compliant P2P lending system also attracts MSMEs that are committed to the halal economy, although there is a need for improvement in the transparency aspect.